Dual chiral structures in the cuticle of Protaetia mirifica analyzed with Mueller matrix spectroscopic ellipsometry - Mendoza-Galván, Arturo; Magnusson, Roger; Jansson, Nicklas; Arwin, Hans; Järrendahl, Kenneth (Frontiers in Physics, 2024)
Many species of beetles from the family Scarabaeidae reflect light with near-circular polarisation. In some cases, spectral narrow-band polarisation phenomena result in a distinct colour with a metallic shine. In other cases, broad-band features are seen, and these beetles have a silvery or goldish appearance. These features in the cuticles originate from helicoidal structures, so-called circular Bragg structures also referred to as Bouligand structures. In this communication, Protaetia mirifica, exhibiting near-circular polarisation properties in dual spectral regions, centred around the wavelengths 474 and 770 nm, is investigated in considerable detail using Mueller-matrix spectroscopic ellipsometry (MMSE). From interference oscillations in the MMSE spectra, the pitch profile of the helicoidal structures in the beetle cuticle is extracted and further used in electromagnetic modelling of the cuticle structure including the determination of epicuticle and exocuticle thicknesses (280 nm and 8.1 μm, respectively), and anisotropic optical properties. These findings are confirmed by scanning electron microscopy. The analysis shows that the uppermost 4 μm of the cuticle has a nearly constant pitch of 310 nm which abruptly jumps to 440 nm and then gradually increases up to 575 nm. Sum decompositions of MMSE spectra reveal that the beetle cuticle reflects like a circular polariser or like a dielectric mirror depending on spectral region.